EVALUATING THE WATER QUALITY OF SOME WELLS IN AL-RIFAI CITY - Hussein Khalefa Chlaib; Reyad Shaker Badeh; Jalal Hamed Ali; Najm Abed Yasir; Alaa Ibrahim Badi; Jaber Hameed Muttair (University of Thi-Qar Journal of agricultural research, 2021)
Due to the scarcity of water resources at the present time in Thi-Qar governorate, many people and farmers resort to using groundwater and well water for all purposes to meet their daily water needs. Therefore, it is important to evaluate the quality of well water and determine its suitability for different uses. Therefore, the researchers in this study dealt with evaluating some physical and chemical properties of the water of some wells located in Al-Rifai city in Thi-Qar governorate / southern Iraq during the year 2020 for the purpose of assessing the quality of well water. Water samples were collected from 9 wells at different depths, ranging between 1-7 meters. The electrical conductivity, pH, turbidity and the total dissolved salts were measured. The concentrations of some major ions in the water of these wells, represented by chloride, carbonate, bicarbonate, calcium and dissolved oxygen, were also measured. Analytical methods were followed for determining chloride ions, bicarbonate, carbonate and calcium, and measuring total dissolved salts (TDS), pH, electrical conductivity (EC), dissolved oxygen (DO) and the turbidity using the electrical methods. It was found that the concentration of ions in the well water for chloride ranged between (31.6 - 3.8 meq / L) and calcium (43.26 - 71.8 meq / L), while the bicarbonate values ​​ranged between (630 - 160 meq / L). The pH values ​​ranged between (7.38 - 7.5) and the EC values between (4.35 - 1.33 mmho / cm), while the values ​​of the TDS ranged between (2175 - 666 ppm) and the DO values ​​ranged between (8.85 - 7.30 ppm). The turbidity values ranged between (FTU 105 - 0.05 FTU). It was found through the study that the values ​​of some ions were high, while others were within the permissible limits, and this indicates contamination of well water in that area. It was also found that the behavior of that water was a basic behavior. All physical and chemical properties were represented in the form of contour maps to illustrate the general distribution of these values ​​in the wells of the study area.